SN 2013fs and SN 2013fr: exploring the circumstellar-material diversity in Type II supernovae. Issue 2 (9th January 2018) - Bullivant, Christopher; Smith, Nathan; Williams, G Grant; Mauerhan, Jon C; Andrews, Jennifer E; Fong, Wen-Fai; Bilinski, Christopher; Kilpatrick, Charles D; Milne, Peter A; Fox, Ori D; Cenko, S Bradley; Filippenko, Alexei V; et al.
Abstract: We present photometry and spectroscopy of SN 2013fs and SN 2013fr in the first ∼100  d post-explosion. Both objects showed transient, relatively narrow H α emission lines characteristic of SNe IIn, but later resembled normal SNe II-P or SNe II-L, indicative of fleeting interaction with circumstellar material (CSM). SN 2013fs was discovered within 8 h of explosion; one of the earliest SNe discovered thus far. Its light curve exhibits a plateau, with spectra revealing strong CSM interaction at early times. It is a less luminous version of the transitional SN IIn PTF11iqb, further demonstrating a continuum of CSM interaction intensity between SNe II-P and SNe IIn. It requires dense CSM within 6.5 × 10 14  cm of the progenitor, from a phase of advanced pre-SN mass loss beginning shortly before explosion. Spectropolarimetry of SN 2013fs shows little continuum polarization (∼0.5 per cent, consistent with zero), but noticeable line polarization during the plateau phase. SN 2013fr morphed from an SN IIn at early times to an SN II-L. After the first epoch, its narrow lines probably arose from host-galaxy emission, but the bright, narrow H α emission at early times may be intrinsic to the SN. As for SN 2013fs, this would point to a short-lived phase of strong CSM interaction if proven to be intrinsic, suggesting a continuum between SNe IIn and SNe II-L. It is a low-velocity SN II-L like SN 2009kr, but more luminous. SN 2013fr also developed an infrared excess at later times, due to warm CSM dust that requires a more sustained phase of strong pre-SN mass loss.